Shape-Engineering and Mechanism Investigation of AgCl Microcrystals - Chunli Cai; Qian Wang; Changsheng Yin; Xuhuan Li; Rong Yang; Xiaodong Shen; Wenbo Xin (Crystals)
AgCl microcrystals are used in visible light photocatalysis. However, their properties depend strongly on the morphology of the crystals and the degree of exposure of the crystal planes. Despite extensive research conducted on the synthesis of AgCl microcrystals, the majority of existing studies have focused on the stable growth of crystals. The role of Cl− ions concentration as a key factor controlling the microcrystals morphology has not been fully explored, which limits the precise tuning of the morphology of AgCl microcrystals. In this study, AgCl microcrystals with controllable morphology are successfully synthesized by a facile solvothermal method. During the preparation process, ethylene glycol (EG) is utilized as a solvent, while polyvinylpyrrolidone (PVP) is employed as a surfactant. We systematically investigate the etching mechanism of AgCl microcrystals by analyzing the effect of sodium chloride (NaCl) concentration on their morphology. This investigation involves the integration of diverse characterization methods, including scanning electron microscopy (SEM), X-ray diffraction (XRD), energy-dispersive X-ray spectroscopy (EDS), and geometrical struc-ture analysis. The results demonstrate that Cl− functions as both a surfactant, thereby promoting the nucleation of cubic microcrystals, and as an etchant, selectively etching the crystal surface. The order of selective etching on the crystal surface follows (100) planes > (110) planes > (111) planes. Based on this new mechanism, AgCl microcrystals with various morphologies, such as cube, octopod and dendrite, are successfully prepared, which provides a new idea for the precise design of noble metal halide microcrystals.